Non-human primates as indicators of Kinetoplastida diversity in an urban environment in Midwest Brazil - Júnior, Oscar Fernandes; Jansen, Ana Maria; Macedo, Gabriel Carvalho de; Nantes, Wesley Arruda Gimenes; Santos, Filipe Martins; Sano, Nayara Yoshie; Barreto, Wanessa Teixeira Gomes; Assis, William Oliveira de; Liberal, Sany Caroline; Xavier, Samanta Cristina das Chagas; Alves, Fernanda Moreira; Dario, Maria Augusta; et al. (Frontiers in Parasitology, 2025)
IntroductionTrypanosomatids are parasites widely distributed in nature, parasitizing several host species in single or co-infections. Campo Grande (CG), capital of Mato Grosso do Sul State, is characterized by several green areas and forest fragments where wild mammals have been reported infected by diverse trypanosomatid species. In this study, we evaluated the parasitism by trypanosomatids in the non-human primates (NHP) Sapajus cay and Alouatta caraya sampled in three different areas of CG.Material and methodsFor the detection of infections and identification of trypanosomatid species, we made hemoculture, blood smears, molecular and serological tests.ResultsWe detected trypanosomatids in 37/55 (67.3%) of sampled animals, all by the molecular test. DNA sequencing analyzes were performed on 32 samples, resulting in the following species identification: Trypanosoma cruzi, T. minasense, T. rangeli, Leishmania (L.) infantum and L. (L.) amazonensis (species already recorded in primates in Latin America), and for the first time T. lainsoni, a parasite related to small mammals, and Trypanosoma sp. DID, originally reported in marsupials Didelphis sp. DiscussionThe detection of trypanosomatids of public health importance as L. infantum, L. amazonensis and T. cruzi (genotypes TcI, TcII/TcVI and TcIV) indicates the enzootic character of these species in the studied area. Also, the presence of T. cruzi TcIV and T. minasense in the conservation area supports previous studies that these parasites would be associated with the arboreal stratum. We conclude that (i) the NHP at CG participate in a complex reservoir system for parasites of great importance for Public Health in the studied area, such as L. infantum, L. amazonensis and T. cruzi, and (ii) there is a great diversity of trypanosomatids circulating in the urban area of this city located in the Brazilian Midwest.